Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1139/o98-012
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional aspects of G protein-coupled receptor oligomerization

Abstract: G protein-coupled receptors (GPCRs) represent the single largest family of cell surface receptors involved in signal transduction. It is estimated that several hundred distinct members of this receptor family in humans direct responses to a wide variety of chemical transmitters, including biogenic amines, amino acids, peptides, lipids, nucleosides, and large polypeptides. These transmembrane receptors are key controllers of such diverse physiological processes as neurotransmission, cellular metabolism, secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(75 citation statements)
references
References 47 publications
2
71
0
2
Order By: Relevance
“…LZ motifs mediate dimer formation via a coiled-coil arrangement of parallel ␣-helices, and are found in many eukaryotic transcription factors (Landschulz et al 1988). Although it is well established that many cell surface receptors mediate their action as dimers (Hebert and Bouvier 1998), it remains to be determined whether CD151 exists and functions as homodimer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LZ motifs mediate dimer formation via a coiled-coil arrangement of parallel ␣-helices, and are found in many eukaryotic transcription factors (Landschulz et al 1988). Although it is well established that many cell surface receptors mediate their action as dimers (Hebert and Bouvier 1998), it remains to be determined whether CD151 exists and functions as homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…LZ motifs mediate dimer formation via a coiled-coil arrangement of parallel ␣-helices, and are found in many eukaryotic transcription factors (Landschulz et al 1988). Although it is well established that many cell surface receptors mediate their action as dimers (Hebert and Bouvier 1998), it remains to be determined whether CD151 exists and functions as homodimer.Although the precise function of CD151 in the brain has not yet been defined, studies in haemopoietic cell lines have indicated an important role of CD151 in an array of fundamental cellular processes, including cell motility (Yauch et al 1998), cell adhesion (Fitter et al 1999, angiogenesis, and vesicular transport of integrins ). In addition, CD151 has been shown to serve as an adaptor or scaffolding protein to attach integrin subunits to other intracellular signaling molecules, such as phosphatidylinositol 4-kinase (PI 4-K) (Yauch et al 1998) and ␣-and ␤-isozymes of protein kinase C (PKC) (Hemler 1998).…”
mentioning
confidence: 99%
“…The formation of dimers for tyrosine kinase receptors is well assessed but it has only recently been proposed for G proteincoupled receptors (for a review and a comment see [14,15]). Recent evidence that some members of the SSTRs family undergo heterodimerization [16] is in line with our result.…”
Section: Discussionmentioning
confidence: 99%
“…Data from microscopy, covalent cross-linking, and x-ray crystallography experiments have revealed that cell surface receptors from many structural classes assemble into multi-receptor complexes; these include some heptahelical G-protein coupled receptors (GPCRs), [36][37][38] methyl-accepting chemotaxis proteins (MCPs), [39] gated ion channels, [40] receptor protein tyrosine kinases (RPTKs), [41,42] and multichain immune recognition receptors (MIRRs). [22,33,35,[43][44][45] The size of these ensembles varies: Some complexes are composed of two receptors while others contain thousands.…”
Section: Signaling Complexesmentioning
confidence: 99%
“…[49] For example, helix-mediated multimerization is proposed to mediate the dimerization and oligomerization of GPCRs (Figure 2). [38,50,51] Evidence for the functional importance of these interactions is suggested by engineering disrupting mutations in the proposed contact sites or by adding isolated transmembrane helices to GPCRs. [37,52,53] Although their effects on receptor oligomerization are not yet well-established, these manipulations modulate signaling; presumably, they disrupt receptor-receptor contacts.…”
Section: Signaling Complexesmentioning
confidence: 99%